Kielitieto kielitaitoon pyrittäessä : vieraiden kielten opettajien käsityksiä kieliopin oppimisesta ja opettamisesta - Jaakkola, Hanna (1997)
The purpose of the study was to investigate the role of grammar in communicative foreign language learning and teaching at secondary level as seen by experienced, expert Finnish foreign language teachers. The research questions dealt with 1) the learning of grammar, 2) the teaching of grammar, and 3) the relationship between grammatical language knowledge and communicative language ability. The subjects were all the foreign language teachers (n=94) at lower and upper secondary levels in the seven Finnish teacher training schools associated with university departments of teacher education. The data collecting instruments consisted of a questionnaire and semi-structured interviews. The questionnaire was used to gather both quantitative and qualitative data. To gain more insight into the matter, six individual teachers were interviewed. Most of the teachers considered foreign language grammar learning to follow the general principles of cognitive learning, rather than to be a special case of learning. Explicit learning was preferred to implicit learning. The teachers considered learning to be most efficient when pupils discovered and constructed the rules of language themselves, guided by the teacher. They also thought that abundant exposure, meaningful practice, time and insight were needed to turn explicit grammatical language knowledge into communicative language ability. The findings indicate that these teachers believe in the importance and usefulness of the explicit teaching of grammar. The teachers' conceptions appear to be consistent with the general cognitive-constructivist view of learning, the cognitive theories of skill learning, and the principles of communicative language teaching. The teachers do not seem to be aware of any linguistic constraints in the cognitive theory, such as the developmental sequences. The implications of the findings for pre-service and in-service teacher education, and for development of language teaching are discussed.